Implementation of Village Financial Administration Management Using the SISKEUDES (Village Financial System) Application in Makeruh Village - Syahrizal, Muhammad; Pribadi, Rizky Maulana (Universitas Syiah Kuala, 2025)
The study examined the implementation of a village financial system using a village financial application. This research is a descriptive qualitative study. The study involved Makeruh Village, Rupat District, Bengkalis Regency. Data collection was conducted through observation, interviews, and documentation. Village financial management in Makeruh Village complies with the Standard Operating Procedure (SOP), specifically Regulation of the Minister of Home Affairs of the Republic of Indonesia Number 20 of 2018 concerning Village Financial Management. Village financial management in Makeruh Village includes planning, implementation, administration, and reporting. Makeruh Village is transparent and accountable in managing village finances. Village financial management using a village financial system improves the villages reporting system.